Spectrum of Neurological Diseases in Tertiary Care Centre of Nepal - Pokharel, Babu Ram; Amatya, Sanu Raja (Nepal Journal of Neuroscience, 2019)
Neurological cases in Nepal are not reported much. Neurological diseases are associated to poor health outcomes including mortality, disability and hospitalization. Epidemiology and clinical pattern of neurological disorders in developing countries remain largely unknown. This is a descriptive study to understand the burden of disease faced by neurologists and internists in a hospital of Nepal. This is a retrospective study of medical records of patients admitted in the Neurology unit of medical ward of Dhulikhel Hospital. A total of 318 patients were admitted during the period of July 2014to January 2015. Diagnosis was established by clinical, radiological, nerve conduction studies, electroencephalography and cerebrospinal fl uidanalysis. A total of 318 patients records during the above mentioned period were reviewed. Common neurological diseases identified were vascular: 138(43.40%); seizure: 60(18.87%); infectious: 20(6.29%); demyelinating: 12(3.77%); degenerative: 14(4.40%); peripheral neuropathy:14(4.40%); and others (mass lesion, ataxia, myelopathy) 60(18.87%). Cerebrovasculardisease is the most common cause of admission of patients in the neurological unit of the hospital. There are differences in the neurological diseases with respect to age, gender and ethnicity.